“Pengaruh Citra Merek Terhadap Loyalitas Konsumen Coca Cola” (Studi Pada Konsumen Coca Cola di Kota Malang) - Raka Kurnia Wicaksono; Ananda Sabil Hussein (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This study aims to determine the effect of variable Brand Image (Corporate Image, User Image and Product Image) on Consumer Loyalty in soft drinks Coca Cola (Coca Cola Studies on consumers in Malang). This study using explanatory method that aims to determine the causal relationship between dependent and independent variables through partial and simultaneous hypothesis testing. The sampling technique used is probability sampling based on the opinions expressed by Roscoe and 150 respondents in the sample obtained from a population of Malang. Regression analysis showed that the variable Brand Image (Image Makers, Image User and Product Imagery) has a significant influence on customer loyalty. Testing hypotheses simultaneously, partial and dominant indicates that the independent variables affect the dependent variable. The correlation coefficient indicates that the correlation between dependent and independent variables are positive and strong. Keywords: Brand Image, Citra Merek, Corporate Image, User Image and Product Image, Consumer Loyalty